TOWARDS AN INCLUSIVE UNIVERSITY EDUCATION: REALITY AND CHALLENGES - Alcaín Martínez, Esperanza (2017)
It is a reality that the International Convention on the Rights of Persons with Disabilities recognizes the right to inclusive education. This reality is regulated by the General Law on the rights of persons with disabilities and their social inclusion. It is also a fact that university education is part of the Spanish education system and the  provisions in the legislation on education are applicable to it. However, this basic and objective approach does not match the situation in which students with disabilities and other specific educational support needs who enter university find themselves in. In that sense, the objective of this paper is to analyze the Spanish university education system to make a diagnosis of the reality and the pending challenges to achieve an inclusive university education.